“DESCALIFICACION DE OFERENTES EN LA ETAPA PRECONTRACTUAL: PROCESOS DE LICITACION” - García Avalos, David Rafael (2019)
The purpose of this research work is to determine the reasons for disqualification of bidders in bidding processes during the pre-contractual stage of the National System of Public Procurement. To this end, a literature and literature review has been developed, information and results have become an intrinsic instrument for the achievement of research work. In the same way, the research is based on the Organic Law of the National System of Public Procurement (LOSNCP) and the specifications of the different processes. Likewise, the methodology used was of a qualitative nature, the data were collected according to the information stipulated by the SERCOP, and in the bidding process completed. For this, the data for the years 2013 to 2017 are shown, analyzing a total of 243 suppliers that participate in the hiring process. However, the information was determined between the reasons for disqualification, the first, the omission or non-compliance with the requirements demanded by the specifications of each process; Then it was evident that the bidders present a personal technique, however, it is a cause of cancellation; Finally, another of the disqualification parameters is related to the economic offer. However, it is necessary to emphasize that these reasons are deployed others that also influence as determinants of disqualification. In addition to what is important that the public institution hires the ideal provider, it makes a thorough review, taking into consideration that the economic offer is a significant element in the process, it is necessary to contemplate each one for the suitable development of the work, as provision, technical liquidity, congruence and experience.